The Nature Conservancy; The National Park Service (Symphony in the Flint Hills, 2015)
The Nature Conservancy works in all fifty states and more than thirty-five countries to conserve the lands and waters on which all life depends . Since 1916, the American people have entrusted the National Park Service with the care of their national parks .
Keywords: nature; conservancy; National Park Service; government; grassland; prairie